CREATIVE APPROACH TO DIAGNOSTIC METHODS IN TECHNOLOGY EDUCATION - HONZIKOVA, Jarmila (Trends in education, 2016)
The article deals with a creative approach to diagnostic methods in technology education. It points out various kinds of pedagogical control, functions of assessment; it focuses on the ways how to assess practical activities in technology education. It specifies some of the negative elements in the assessment of pupils' performance and suggests how to improve the assessment.
Keywords: diagnostic methods; assessment of practical activities